2022
DOI: 10.20944/preprints202207.0087.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional Components of Millet Porridge Cooked by Different Electric Cookers based on Principal Component and Cluster Analyses

Abstract: (1) Background: In order to study the effects of different electric cookers on the nutritional components of millet porridge, five different electric cookers were selected to cook millet porridge, and sensory and nutritional components in millet porridge, millet soup, and millet grains were analyzed. (2) Methods: Using principal component and cluster analysis, a variety of nutritional components were comprehensively compared. (3) Results: The results showed that among the different cooked samples, the content … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Free fatty acids (especially unsaturated fatty acids) are unstable, which will further form hydroperoxide free radicals, and then trigger a series of cyclization, oxidation, cracking and other reactions, producing volatile components such as aldehydes, ketones, alcohols, and acids [ 15 ]. Zhang et al [ 44 ] found that the volatile components of millet soup and millet porridge cooked in the same electric cooker are more similar, and the aroma is stronger, indicating that fatty acids are degraded into volatile components. The content of fatty acids in millet grain is higher, corresponding to the lighter aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Free fatty acids (especially unsaturated fatty acids) are unstable, which will further form hydroperoxide free radicals, and then trigger a series of cyclization, oxidation, cracking and other reactions, producing volatile components such as aldehydes, ketones, alcohols, and acids [ 15 ]. Zhang et al [ 44 ] found that the volatile components of millet soup and millet porridge cooked in the same electric cooker are more similar, and the aroma is stronger, indicating that fatty acids are degraded into volatile components. The content of fatty acids in millet grain is higher, corresponding to the lighter aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the relative content of ethanol dimer and acetic acid monomer was the highest, and MCW had the highest content of acetic acid monomer (18.28%) and the lowest content of ethanol dimer (21.60%) compared to the other three samples. Alcohols and acids generally have higher thresholds and contribute less to the flavor of coconut water, but this may be one of the reasons for the poor taste of MCW [53][54][55][56]. Esters are the products of esterification reactions between organic acids and alcohols, which mainly impart milky, fruity, and oil-like flavors to the product [48][49][50].…”
Section: Analysis Of Volatile Organic Compoundsmentioning
confidence: 99%
“…Glutaraldehyde has a certain fruit aroma, while hexanal and nonanal have a sweet aroma of grass. Heptanal has both oil and fruit aromas [53][54][55]. The aldehydes of coconut water were dominated by nonanal, and the relative contents of nonanal dimer and monomer ranged from 0.85% to 1.43% and from 2.79% to 7.13%, respectively.…”
Section: Analysis Of Volatile Organic Compoundsmentioning
confidence: 99%